2013
DOI: 10.1038/bjc.2013.188
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin-induced methylation of the ABCG2/BCRP promoter as a novel mechanism to overcome multidrug resistance in brain tumour stem cells

Abstract: Background:Current evidence indicates that a stem cell-like sub-population within malignant glioblastomas, that overexpress members of the adenosine triphosphate-binding cassette (ABC) family transporters, is responsible for multidrug resistance and tumour relapse. Eradication of the brain tumour stem cell (BTSC) compartment is therefore essential to achieve a stable and long-lasting remission.Methods:Melatonin actions were analysed by viability cell assays, flow cytometry, quantitative PCR for mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 25 publications
3
94
0
Order By: Relevance
“…It has been reported that demethylation of the ABCG2 promoter is related to reactivation of the gene and the subsequent ABCG2-dependent MDR phenotype (26,45). To this end, drug-induced epigenetic modulation of the ABCG2 gene has attracted increasing attention recently (45)(46)(47). Our data showed for the first time that afatinib induced methylation of the ABCG2 promoter, thus leading to a decrease in mRNA level of ABCG2 in S1-MI-80 cells, which has not been reported with other TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that demethylation of the ABCG2 promoter is related to reactivation of the gene and the subsequent ABCG2-dependent MDR phenotype (26,45). To this end, drug-induced epigenetic modulation of the ABCG2 gene has attracted increasing attention recently (45)(46)(47). Our data showed for the first time that afatinib induced methylation of the ABCG2 promoter, thus leading to a decrease in mRNA level of ABCG2 in S1-MI-80 cells, which has not been reported with other TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Martin and colleagues observed that melatonin markedly increased the cancer killing activity of temozolomide, doxorubicin or mitoxantrone [18]. Their study indicated that co-incubation of melatonin plus a chemotherapeutic drug resulted in a synergistic inhibitory action in the three BTSC lines (NSC23, NSC7-2 and NSC11) tested.…”
Section: The Impact Of Melatonin On Tumor Stem Cells Melatonin Inhibimentioning
confidence: 99%
“…Thus, a therapeutic strategy that targets both the tumor bulk and the brain tumor stem cell (BTSC) compartment is essential to bring about a stable and enduring remission [18].…”
Section: The Impact Of Melatonin On Tumor Stem Cells Melatonin Inhibimentioning
confidence: 99%
See 1 more Smart Citation
“…Quiescence is associated with cancer stem cells, a subpopulation of cancer cells that are critical for tumor progression (24)(25)(26). Tumor stem cells were reported primarily at the status of quiescence (27,28). Differentiation of tumor stem cells may lead to the loss of quiescent status (29,30).…”
Section: Discussionmentioning
confidence: 99%